Lesbianidade no front: gênero, raça, performances e silenciamentos na Polícia Militar do Estado da Bahia - Lopes, Regina Trindade (2023)
The central objective of this thesis is to understand the scope of the decentering of lesbian performances from the control device, which permeates public security by normalizing female subalternity, and naturalizes the standard male model in the Military Police of the State of Bahia (PMBA). The hypothesis that the denial of the feminine, as well as the offensive against performances that are dissident to the norm, within the scope of performativity, is part of the discourse of military belonging that names and sanctions what and who can be “acceptable” and “not acceptable”, exposing the institutional demand for a masculinity based on the warrior and savage ethos. This thesis, by focusing on lesbian performances and activating the voices of decolonial black intellectuals, problematizes how the military forces use their tools to accommodate them, cool them down, and, at times, reward them for their distinction from other women, focusing on master their languages, imposing new narratives of continuous control of bodies, life, death, and subjectivities both inside and outside the military police institution, in a mirror of Public Security in the State of Bahia. The research, based on an autoethnobiographical basis associated with the continuum of biographical narratives of lesbian military police officers, highlighted gender inequality crossed by intersections of gender, race, social class and sexuality, through the different existences of lesbian police officers who narrated their experiences in situations of harassment, isolation, walling in and silencing imposed on women, lesbians and black women.